2020
DOI: 10.1080/24732850.2020.1756676
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Structured Risk Assessment Guidelines: Development and Preliminary Evaluation of an Adherence Scale for the START:AV

Abstract: Risk assessment instruments are widely used to predict risk of adverse outcomes, such as violence or victimization, and to allocate resources for managing these risks among individuals involved in criminal justice and forensic mental health services. For risk assessment instruments to reach their full potential, they must be implemented with fidelity. A lack of information on administration fidelity hinders transparency about the implementation quality, as well as the interpretation of negative or inconclusive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…In one study, assessors initially left an average of three risk estimates blank or missing per assessment, but missing estimates decreased after this finding was identified and discussed with assessors (Desmarais et al, 2012). Similarly, De Beuf, de Vogel, and de Ruiter (2020) found that scores on an 11-item adherence tool significantly increased after assessors attended a refresher training.…”
Section: Barrier 1: Challenges In the Implementation Of Risk Assessme...mentioning
confidence: 87%
See 1 more Smart Citation
“…In one study, assessors initially left an average of three risk estimates blank or missing per assessment, but missing estimates decreased after this finding was identified and discussed with assessors (Desmarais et al, 2012). Similarly, De Beuf, de Vogel, and de Ruiter (2020) found that scores on an 11-item adherence tool significantly increased after assessors attended a refresher training.…”
Section: Barrier 1: Challenges In the Implementation Of Risk Assessme...mentioning
confidence: 87%
“…Although Proctor et al’s (2011) taxonomy provides a starting point for understanding what to measure (e.g., acceptability), as a next step, researchers need to develop instruments that map onto these outcomes. In a recent study, De Beuf et al (2020) created a fidelity tool with good interrater reliability. However, formal measures of other implementation outcomes, such as appropriateness and feasibility, are lacking.…”
Section: A Road Map For Future Researchmentioning
confidence: 99%
“…In an early field study with the HCR‐20, Belfrage (1998) actually excluded an evaluator from the reliability analyses, because this person scored significantly differently from the other clinicians, arguably due to a gap of 6 months between the training and the risk assessments. That said, in the present setting, some evaluators participated in a refresher workshop that took place halfway through the data collection period (De Beuf et al, 2020). This may have reduced rater drift, although the sample was too small to explore this further.…”
Section: Discussionmentioning
confidence: 99%
“…In the intervention literature, researchers have developed checklists to assess implementation fidelity of a practice of interest. Likewise, we developed a scale to assess the level of completion of START:AV rating forms: the START:AV Adherence Rating Scale (STARS; De Beuf, de Vogel, & de Ruiter, 2020). This scale codes how complete the rating forms are, but does not investigate the quality of the ratings as measured by the descriptors listed in the user guide.…”
Section: Discussionmentioning
confidence: 99%